Incidence and predictors of post-transplant lymphoproliferative disease after kidney transplantation during adulthood and childhood: a registry study. Issue 5 (12th January 2018) - Francis, Anna; Johnson, David W; Teixeira-Pinto, Armando; Craig, Jonathan C; Wong, Germaine
ABSTRACT: Background: Differences in the epidemiology of post-transplant lymphoproliferative disease (PTLD) between adult and paediatric kidney transplant recipients remain unclear. Methods: Using the Australian and New Zealand Dialysis and Transplant Registry (1963–2015), the cumulative incidences of PTLD in children (age <20 years) and adults were calculated using a competing risk of death model and compared with age-matched population-based data using standardized incidence ratios (SIRs). Risk factors for PTLD were assessed using Cox proportional hazards regression. Results: Among 23 477 patients (92% adult, 60% male), 505 developed PTLD, with 50 (10%) occurring in childhood recipients. The 25-year cumulative incidence of PTLD was 3.3% [95% confidence interval (CI) 2.9–3.6] for adult recipients and 3.6% (95% CI 2.7–4.8) for childhood recipients. Childhood recipients had a 30-fold increased risk of lymphoma compared with the age-matched general population [SIR 29.5 (95% CI 21.9–38.8)], higher than adult recipients [SIR 8.4 (95% CI 7.7–9.2)]. Epstein–Barr virus (EBV)-negative recipient serology [adjusted hazard ratio (aHR) 3.33 (95% CI 2.21–5.01), P < 0.001], year of transplantation [aHR 0.93 for each year after the year 2000 (95% CI 0.88–0.99), P = 0.02], induction with an agent other than anti-CD25 monoclonal antibody [aHR 2.07 (95% CI 1.16–3.70), P = 0.01] and having diabetes [aHR 3.49 (95% CI 2.26–5.38), P < 0.001] were independently associated with PTLD. Conclusions: Lymphoma occurs at similar rates in adult and paediatric recipients, but has been decreasing since the year 2000. EBV-negative patients and those with diabetes or induction agent other than anti-CD25 monoclonal antibody are at substantially increased risk of PTLD.